A Analisis Pola Perilaku Self Care Pada Pasien Hipertensi Patuh Pengobatan Dengan Pendekatan Health Belief Model - Khairunisa, Aisya Fitri; Yuwindry, Iwan; Mukti, Yusuf Anggoro; Syamsu, Erlina (LPPM Universitas Sari Mulia, 2024)
Background: The increasing prevalence of hypertension has become a major concern of global health. Key aspects of hypertension management include medication adherence and non-pharmacological interventions such as self-care and health belief model. However, public awareness regarding hypertension management remains low.Objective: Analyze the pattern of self-care behavior in hypertensive patients with medication compliance indicators by applying health belief model approach.Methods: Type and design of the study used was observational analysis with a cross sectional design. The sampling technique is purposive sampling. Sample in this study is 45 respondents consisting of 37 women and 8 men. Data collection was carried out by interviews using questionnaires and analysis spearman rank test with a degree of significance (α) = 0.05.Results: Bivariate analysis obtained the perception susceptibility (p value = 0.000 ; rho = 0.796), perception severity (p value = 0.000 ; rho = 0.858), perception benefit (p value = 0.000 ; rho = 0.752), perception barriers (p value = 0.000; rho = 0.747), cues to act (p value = 0.000; rho = 0.781), self-efficacy (p value = 0.000; rho = 0.714), value and attitude (p value = 0.000; rho = 0.726), social support (p value = 0.000; rho = 0.593).Conclusions: There was a relationship between perception of susceptibility, severity, benefits, barriers, cues to act, self-efficacy, values and attitudes, social support in control behavior with indicators of compliance hypertensive patients of productive age (26-45 years) in the working area of Public Health Center Sungai Tabuk 1.